BONE MINERAL DENSITY DETERMINATION BY SKELETAL MATURITY OF YOUNG ATHLETES - ŠELINGEROVÁ M; DOLEŽAJOVÁ L.; ŠELINGER P.; SEDLÁČEK J. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2015)
The article is focused on level determination of skeletal maturity and bone density mineralization of pubescent and adolescent athletes. Bone mineral content and density (BMC, BMD) at the left hip (LH) and lumbar spine (LS) we found by dual x-ray absorptiometry and skeletal maturity according TW3 method (Tanner et al., 2001) in 99 young athletes (49 boys aged 14.2 ± 1.42 and 50 girls aged 13.7 ± 1.06). Results were compared to reference values of ordinary population (z-score). The relation between the bone indicators and the bone age, taking into account the physical growth of athletes, was analyzed with the help of correlation coefficients. The average BMC, BMD values were higher in athletes than in ordinary population. In boys, higher degree of mineralization was found in left hip area (LH total) than in lumbar spine (LS total). In girls, the z-score results of the both monitored parameters were nearly the same. In group of boys there was found significant relationship between the bone age and bone mass parameters, LS and LH (p < 0.05 to p < 0.01); but lower values were found in group of girls. Similar differences between boys and girls were confirmed also in correlation coefficients between the body weight and z-scores in both lumbar (LS) and left hip (LH) areas. Trends of bone mineralization indicators, assessed in dependence on the bone age, unanimously indicate differences between the boys and girls. Also the curve trends indicate that the dynamism of the total mineralization growth, and strength of bones is higher in boys, and this process runs linearly until the adulthood. The dynamism of mineralization processes in girls culminates after the 14th year of age.